Estratégias de acasalamento e qualidade do espermatóforo em heliconius (Lepidoptera, Nymphalidae) - Silva, Emmanuelle Séfora Cabral (2009)
Butterflies are insects known, in a variety of environments and for easy visual identification. The adult form may be frequently found in flowers looking for nectar. However, for many species of Heliconius (Lepidoptera, Nymphalidae) to visit the flower also represents the collecting of pollen, an important source of protein for adults. The protein obtained from the pollen allows the maintenance of physiological processes that increase the performance of the individual, promoting greater longevity and egg production. For males, proteins can also be part in your investment in reproductive success and fitness of offspring through a nutritional contribution that is transferred to the female in the act of mating as a nuptial present. It is known that this protein contains essential to the performance of the female oviposition, however the proportion of content and specific importance to the monogamous and polygamous species is not known yet. Whereas the species studied in this work have different patterns of mating in the strategy was to verify a significant difference in the quality of the spermatophore, and H. erato and H. melpomene, on the amount of protein present in this structure, indicating a difference in investment between the male reproductive strategies